On distribution of Moerckia flotoviana (Moerckiaceae, Marchantiophyta) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Herbarium samples of Moerckia hibernica were revised in KPABG, LE and H. Most of the c. 70 samples observed are in fact M. flotoviana that was treated as a forma of M. hibernica for a long time. It was shown that M. flotoviana is more widespread than M. hibernica. Distribution map is presented on the basis of reliable literature records and studied specimens. The identification key for the genus Moerckia as well as detailed description of M. flotoviana and its diagnostic features are provided.
Keywords: liverworts, Moerckia flotoviana, distribution, key.